Rancang Bangun Aplikasi Performa Jaringan Komunikasi Fiber Optic (FO) sebagai Salah Satu Media Transmisi Node B (NB) di Area Malang Berbasis Android - Ahmad Maulana Hakim (Jurnal Jaringan Telekomunikasi, 2017)
Fiber optic is chosen to be the backbone channel for telecommunication purposes, in this case the connection between nodes b. Therefore, to determine the performance of a fiber optic network, a fiber optic communication network performance application is required. The performance discussed in this study is total attenuation, Optical Signal to Noise Ratio (OSNR) and Bit Error Rate (BER). The method used to obtain the attenuation value along the length of the cable and the total attenuation is by measuring the fiber optic network with an Optical Time Domain Reflectometer (OTDR). After taking measurements, the data is processed to produce output in the form of network performance, namely the total attenuation value, OSNR and BER. The results of the accuracy of the two comparisons are indicated by the percentage error rate. Based on the overall data tested, a value of 5.53% was obtained for comparison between the theoretical results and the value of the measurement results and obtained a value of 5.10% for the comparison between the measurement value and the application calculation value. Then the relationship between total attenuation with OSNR and the relationship between OSNR and BER is an inverse relationship.